Systematic Y2H Screening Reveals Extensive Effector-Complex Formation - Alcântara, André; Bosch, Jason; Nazari, Fahimeh; Hoffmann, Gesa; Gallei, Michelle; Uhse, Simon; Darino, Martin A.; Olukayode, Toluwase; Reumann, Daniel; Baggaley, Laura; Djamei, Armin (Frontiers in Plant Science, 2019)
During infection pathogens secrete small molecules, termed effectors, to manipulate and control the interaction with their specific hosts. Both the pathogen and the plant are under high selective pressure to rapidly adapt and co-evolve in what is usually referred to as molecular arms race. Components of the host’s immune system form a network that processes information about molecules with a foreign origin and damage-associated signals, integrating them with developmental and abiotic cues to adapt the plant’s responses. In the case of both nucleotide-binding leucine-rich repeat receptors (NLRs), and leucine-rich repeat receptor kinases (LRR-RKs) these networks have been extensively characterized. However, little is known on whether pathogenic effectors form complexes to overcome plant immunity and promote disease. Ustilago maydis, a biotrophic fungal pathogen that infects maize plants, produces effectors that target hubs in the immune network of the host cell. Here we assess the capability of U. maydis effector candidates to interact with each other, which may play a crucial role during the infection process. Using a systematic yeast-two-hybrid (Y2H) approach and based on a preliminary pooled screen, we selected 63 putative effectors for one-on-one matings with a library of nearly 300 effector candidates. We found that 126 of these effector candidates interacted either with themselves or other predicted effectors. Although the functional relevance of the observed interactions remains elusive, we propose that the observed abundance in complex formation between effectors adds an additional level of complexity to effector research and should be taken into consideration when studying effector evolution and function. Based on this fundamental finding, we suggest various scenarios which could evolutionarily drive the formation and stabilization of an effector interactome.